INDIVIDUAL LEARNING PLAN OF A SECONDARY SCHOOL STUDENT: THE BASIS FOR DESIGNING PROFILED EDUCATION AND A CONSCIOUS CHOICE OF PROFESSION - Chehlova, Zoja; Chekhlov, Mikhail; Keviša, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In the 21st century, the search for a new educational paradigm is characteristic of all countries of the European Union. The predominance of the traditional information approach, which is mainly focused on the transfer of knowledge to learners, creates a passive person (Thoresen, 2007). Profiled education represents a new model of the system of education with a student as a subject of the educational process in its center. Within this model, the educational process is organized in accordance with learner’s interests, abilities, and capabilities, i.e., it has a natural character. The key quality of a student within profiled education is his/her subjectness. This quality is formed under the conditions of student’s active, conscious position in the educational process (Čehlovs, 2011). An individual learning plan developed by the student together with the teacher becomes the basis for designing profiled education, which contributes to a conscious choice of profession. The subject of research is the individual learning plan of a senior secondary school student as the basis for designing the content of profiled education and for the conscious choice of profession. The aim of the study is to consider the structure of student’s individual learning plan and to determine its role in the design of profiled education and in the choice of profession. The research methods include theoretical analysis, observation, and survey. As a result of the research, the structure and content of the individual learning plan of a senior secondary school student were determined, and the analysis of the role of the individual learning plan in the design of profiled education and in the conscious choice of profession was carried out.